Integrating Python Programming Within A Multiple Representation Framework To Enhance Student Mathematical Numeracy - Reni Dwi Susanti; Marhan Taufik; Hendarto Cahyono; Buaddin Hasan (Jurnal Pendidikan MIPA, 2026)
By using digital technology, this study aims to develop a learning design that facilitates multiple representations and numeracy skills. The ASSURE model was used as the design approach for this development. The first stage was a needs analysis to ensure the development aligns with the needs of educators and students. A validation stage was also conducted before classroom use to ensure it is applicable and addresses teaching and learning challenges. The method used was a mixed methods approach. The development stage provided an overview of the process, followed by descriptive and inferential statistical analyses to assess the results of the learning design implementation. The results showed that Python-based learning led to a greater increase in numeracy skills than conventional learning. The experimental group increased its average score from 60.12 in the pretest to 83.72 in the posttest, with an N-gain of 0.60, while the control group achieved an N-gain of 0.36. Statistical tests showed that the increase in both groups was significant, but the magnitude of the increase in the experimental group was more dominant. Qualitative findings from observations and questionnaires showed that students became more active, helped their understanding of concepts through various representations, and were more confident in solving numeracy problems, despite initially experiencing difficulties using Python. In addition, expert validation results showed that the developed learning design was in the very feasible category for content, media, and learning. Students demonstrate various types of representations in learning, including graphical, symbolic, pictorial, tabular, and verbal representations. Therefore, it can be concluded that developing a learning environment that aligns with learning objectives and is tailored to each student's skills and conditions can significantly increase student engagement and achieve desired competencies. Keywords: python-based learning design, multiple representation, numeracy skills, digital.